Isolation and Genetic Characterization of Parvoviruses From Dogs, Cats, Minks, and Raccoon Dogs in the Eastern Region of Shandong Province, China - Zhao, Jiakai; Zhang, Hao; Zhang, Lu; Zhang, Qiang; Zhou, Ning; Du, Taofeng; Zhao, Qin; Zhou, En-Min; Du, Yongkun; Sun, Yani (Frontiers in Microbiology, 2022)
The eastern region of Shandong province, China, is an intensive economic mink and raccoon dog breeding area. To investigate the molecular variations of parvovirus in cats, dogs, minks, and raccoon dogs from this region, feline panleukopenia virus (FPV), canine parvovirus 2 (CPV-2), mink enteritis virus (MEV), and raccoon dog parvovirus (RDPV) were separately isolated and characterized from the respective animals with gastroenteritis. PCR amplification showed that there were 15/18 (83.3%), 9/13 (69.2%), 8/11 (72.7%), and 3/7 (42.9%) samples from the diseased animals separately positive for FPV, CPV-2, MEV, and RDPV. Of these, a total of 6 FPV, 6 MEV, 4 CPV-2, and 3 RDPV strains were successfully isolated using F81 cells. Next, the near-complete genomes of 19 parvovirus isolates were amplified and analyzed. The viral particle 2 (VP2) sequence alignment showed that they shared 97.2%-100% nucleotide similarity. Phylogenetic analysis showed that the 5 FPV isolates were in the same branch, and an FPV isolate was closely related with MEV and RDPV isolates obtained in this study. These suggested that cross-species infection occurred in the Shandong region between the FPV, MEV, and RDPV. For the 4 CPV-2 isolates, 3 were antigenic variant strains CPV-2a, and the other was antigenic variant strain CPV-2c. Additionally, the mutations that had emerged in the VP2 amino acids of CPV-2 also occurred in the VP2 from the FPV, MEV, and RDPV isolates. This study suggested that the continuous evolution of the parvovirus may be accelerated in areas with a high density of economic animal trading/breeding, and controlling parvovirus infection in these animals remains a challenge.